رصد تدابير تخفيف الأثر البيئي في منشآة مصفاة بانياس لتكرير النفط - هيثم جناد; عادل عوض; مايا نوح (Tishreen University, 2018)
The oil sector is considered to be one of the most important and influential sectors in the environment, whether through refining, manufacturing, transporting or storing its products or while disposing of the huge quantities of waste. In spite of the precautions, controls and treatment available in the most important oil installations in the Syrian coast (Banias Oil Refinery), the environmental effects of gaseous, liquid or solid oil contaminants will find their way into the general environment, leaving serious negative impacts on the components of different ecosystems -air - soil - groundwater - rivers - sand and beach rocks - etc ..). Therefore, this research is a means of monitoring the environmental measures and Procedures taken in the facility to avoid, reduce and compensate the resulting environmental impacts. A plan was adopted which included a question questionnaire with specific questions distributed to the employees, interviews with specialists and Concerned discussions with members of the surrounding area, To find out Extent of application the environmental safety conditions in the facility and the obstacles it faces to help the results of this study to advise the Ministry of Oil and Mineral Resources and related government agencies to guide the decision-making processes, considering that Syria has become in recent years of countries interested in issuing various environmental regulations to reduce the problems of environmental pollution.                                                                                                                           يعتبر قطاع النفط من أهم وأخطر القطاعات تأثيراً في البيئة، سواء من خلال عمليات تكريره، أو عمليات تصنيع مشتقاته أو عمليات نقله وتخزينه أو أثناء التخلص من الكم الهائل من مخلفاته. وعلى الرغم من اتخاذ الاحتياطات وأدوات التحكم والمعالجة المتاحة في أهم منشآة نفطية في الساحل السوري (مصفاة بانياس لتكرير النفط)، فإن الآثار البيئية الناتجة عن الملوثات النفطية الغازية أو السائلة أو الصلبة تجد طريقها الى البيئة العامة، لتترك آثاراً سلبية خطيرة على مكونات النظم البيئية المختلفة (الهواء - التربة - المياه الجوفية - الأنهار - رمال وصخور الشاطئ - الخ..). لذلك فإن هذا البحث هو وسيلة لرصد التدابير والإجراءات البيئية المتخذة في المنشآة لتجنب وتقليل الآثار البيئية الناتجة، وتم اعتماد خطة تضمنت استمارة استبيان بأسئلة محددة موزعة على العاملين، ومقابلات مع اختصاصيين، ومناقشات معنية مع أفراد المنطقة المحيطة، لمعرفة مدى تطبيق شروط السلامة البيئية في المنشآة والعوائق التي تعترضها لتساعد نتائج هذه الدراسة في تقديم المشورة لوزارة النفط والثروة المعدنية ووكالات الحكومة ذات الصلة بهدف توجيه عمليات صنع القرار على اعتبار أن سوريا أصبحت في السنوات الأخيرة من الدول المهتمة بإصدار الأنظمة البيئية المختلفة للحد من مشكلات التلوث البيئي.